Gerakan Bejiruyung Bersedekah: A Strategy for Cultivating Character Education Values in Bejiruyung Village Community - Ardianzah, Ramadhan Dwi; Musyarofah, Rizkia; Nugraheni, Setyo Wuri Kartika; Trirahayu, Rina Estu (INDONESIAN JOURNAL OF SUSTAINABILITY, 2025)
Character education has a high level of urgency in building a society that is sensitive to the surrounding environment, moral, solid, and has integrity. However, in the current era of modernization, there is an alarming crisis of character education in Indonesian society. This research aims to analyze the cultivation of character education values in the Bejiruyung Village community through the Gerakan Bejiruyung Bersedekah. The research method used is qualitative case study with data collection techniques through interviews and observations. Based on the results of interviews and observations, it can be analyzed that there are character education values instilled in the Bejiruyung Village community through the Gerakan Bejiruyung Bersedekah. The embedded character education values include religion, social care, tolerance, communicative, discipline, and honesty. These values can be attached to the community because the Gerakan Bejiruyung Bersedekah is committed and consistent in spreading benefits and has sustainable programs. The novelty of this research lies in the community-based approach that shows that social activities can serve as an effective tool in character education. The implication is that the results of this study can serve as a reference for the development of character education programs at the local level. Therefore, it is recommended that charity programs be strengthened and integrated into the education curriculum to create a more supportive environment for character building.